2023
DOI: 10.3390/f14040828
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Water and Carbon Estimation Models in the Caatinga Biome Based on Remote Sensing

Abstract: The study of energy, water, and carbon exchanges between ecosystems and the atmosphere is important in understanding the role of vegetation in regional microclimates. However, they are still relatively scarce when it comes to Caatinga vegetation. This study aims to identify differences in the dynamics of critical environmental variables such as net radiation (Rn), evapotranspiration (ET), and carbon fluxes (gross primary production, GPP) in contrasting recovered Caatinga (dense Caatinga, DC) and degraded Caati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…The results gave significantly different evapotranspiration estimates compared to the local kc evapotranspiration estimated for 4 years over 6 (Table 5). These results agree with those of de Oliveira et al [60], who found that evapotranspiration estimated using the SEBAL showed higher differences in relation to the observed values. In contrast, Kaysert et al [61] reported that daily estimates of geeSEBAL yielded an average RMSD of 0.91 mm/day when compared to eddy covariance system data, while Gonçalves et al [62] indicated that geeSEBAL has significant potential for use in the assessment of crop evapotranspiration for irrigation monitoring and management in Brazil, even in areas with missing climate data.…”
Section: Maize Daily Actual Evapotranspirationsupporting
confidence: 93%
“…The results gave significantly different evapotranspiration estimates compared to the local kc evapotranspiration estimated for 4 years over 6 (Table 5). These results agree with those of de Oliveira et al [60], who found that evapotranspiration estimated using the SEBAL showed higher differences in relation to the observed values. In contrast, Kaysert et al [61] reported that daily estimates of geeSEBAL yielded an average RMSD of 0.91 mm/day when compared to eddy covariance system data, while Gonçalves et al [62] indicated that geeSEBAL has significant potential for use in the assessment of crop evapotranspiration for irrigation monitoring and management in Brazil, even in areas with missing climate data.…”
Section: Maize Daily Actual Evapotranspirationsupporting
confidence: 93%
“…Other studies showed that semiarid regions present representative values of AGB, as in the case of agriculture-pasture mosaics [7][8][9]. Monitoring the AGB variation in agriculture-pasture mosaics may indicate changes in vegetation cover, loss of biodiversity, or soil degradation.…”
Section: Statistics By Each Lulc Classmentioning
confidence: 99%
“…Forests and family farming contribute to carbon sequestration, while mechanized agriculture can lead to greenhouse gas emissions [1][2][3]. While the mapping of carbon storage and sequestration has been extensively studied in forest regions [4][5][6], there is a lack of research focusing on semiarid areas [7][8][9] and on estimating carbon in different types of vegetation, including regions with agricultural activities [10].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, studies with larger spatial and/or temporal scales are conducted using remote sensing data [4,18,24,25] or via modeling [2,[26][27][28][29][30]. Studies using soil-vegetationatmosphere transfer (SVATS) models are a viable alternative for determining and evaluating energy and CO 2 fluxes in various ecosystems.…”
Section: Introductionmentioning
confidence: 99%